Re-rolling treatment in the fermentation process improves the taste and liquor color qualities of black tea - Qincao Chen; Ying Fu; Wenting Heng; Shuai Yu; Feng Xie; Fang Dong; Zhi Lin; Weidong Dai; Haihui Fu (Food Chemistry: X, 2024)
Fermentation is a vital process occurred under the premise of rolling affecting black tea quality. Theoretically, re-rolling during fermentation will remodel the biochemical conditions of tea leaves, and thus influence black tea quality. Herein, we studied the effect of re-rolling on black tea taste and liquor color. Sensory evaluation showed that re-rolling significantly weakened the astringency taste and improved the redness and luminance of liquor. With re-rolling, the color attributes of a* and L* and the contents of theaflavins and thearubigins were significantly improved. Metabolomics analysis showed that the contents of 110 non-volatile compounds were significantly different among black teas with different rolling treatments. In summary, re-rolling accelerated the oxidation of polyphenols into pigments, the hydrolysis of proteins into amino acids, and the metabolism of alkaloids, organic acids, glycosidically-bound volatiles, and lipids during the fermentation period. Our study provided a novel and simple way to improve black tea quality.